The Hydrogen Sulfide Releasing Molecule Acetyl Deacylasadisulfide Inhibits Metastatic Melanoma - De Cicco, Paola; Panza, Elisabetta; Armogida, Chiara; Ercolano, Giuseppe; Taglialatela-Scafati, Orazio; Shokoohinia, Yalda; Camerlingo, Rosa; Pirozzi, Giuseppe; Calderone, Vincenzo; Cirino, Giuseppe; Ianaro, Angela (Frontiers in Pharmacology, 2017)
Abstract Melanoma is the most common form of skin cancer. Given its high mortality, the interest in the search of preventive measures, such as dietary factors, is growing significantly. In this study we tested, in vitro and in vivo, the potential anti-cancer effect of the acetyl deacylasadisulfide (ADA), a vinyl disulfide compound, isolated and purified from asafoetida a foul-smelling oleo gum-resin of dietary and medicinal relevance. ADA markedly suppressed proliferation of human melanoma cell lines by inducing apoptosis. Moreover, treatment of melanoma cells with ADA reduced nuclear translocation and activation of NF-κB, decreased the expression of the anti-apoptotic proteins c-FLIP, XIAP and Bcl-2 and inhibited the phosphorylation and activation of both AKT and ERK proteins, two of the most frequently deregulated pathways in melanoma. Finally, the results obtained in vitro were substantiated by the findings that ADA significantly and dose-dependently reduced lung metastatic foci formation in C57BL/6 mice. In conclusion, our findings suggest that ADA significantly inhibits melanoma progression in vivo and could represent an important lead compound for the development of new anti-metastatic agents.